Perancangan Desain Kemasan Produk Kacang Goreng Renyah Panineungan - Istianah, Raray (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The Panineungan Crispy Fried Beans brand is the flagship product of the Panineungan company, which is a Small, Micro and Medium Enterprise (MSME) in Sukaraja Regency. These fried peanuts have the advantage of being peanuts that have various additional flavors, but the product is not supported by a packaging design which is considered to lack identity product information, but is only packaged in transparent plastic with a printed sticker label, so it has no appeal to consumers. The aim of designing the packaging for the Panineungan Crispy Fried Beans product is an effort to provide product identity and be able to show the product's image compared to other competitors. The design is carried out by displaying product packaging designs with images for middle and upper middle levels. It is hoped that the production of Panineungan Crispy Fried Beans packaging will be able to strengthen the product's identity as a typical regional souvenir of Sukabumi Regency in order to achieve quality Small Micro and Medium Enterprises (MSME) products.